(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Cultural heritage is a subject of interdisciplinary research. Each discipline finds (reveals) its own aspect of research, its own vision of the problem. Narrow subject analysis of the cultural heritage of the peoples of past times already reveals its weak point. There has not yet been a panoramic idea of ​​the specific direction of research of this program. The ideological positions of research groups and the specifics of their cognitive or interpretive activity in different plans are not defined, or rather, are not summarized. There is a lack of bold statement of the general problems of research practice and the discovery of new areas and scientific directions in the state cultural policy.